Analisis Perbedaan Kinerja Keuangan Sebelum dan Sesudah Melakukan Merger dan Akuisisi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2020 - Ramadhani, Husna Desi Lia; Yudiantoro, Deny (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to see differences in financial performance before and after mergers and acquisitions. The financial performance used is 2 years of data before and after making mergers and acquisitions available on the IDX in 2016-2020. The type of approach used is quantitative, with a comparative type of research. The total population amounted to 75 companies, while the sample amounted to 13 issuers using purposive sampling technique. The type of data used is secondary data, in the form of issuer financial statements, all of which data is obtained from the official IDX website. This study uses financial ratios as variables, including liquidity ratios calculated using Current Ratio (CR), activity ratios calculated using Total Asset Turnover (TATO), solvency ratios measured using Debt to Equity Ratio (DER), and there are profitability ratios measured using Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS). The technical analysis used is descriptive statistics and to see the distribution of data using the normality test. Hypothesis testing using the Wilcoxon test, shows the output that DER and EPS have a significance value <0.05, meaning that there are significant differences before and after mergers and acquisitions. While CR, TATO, ROA, ROE and NPM do not show significant differences. Keywords: Financial Performance, Financial Ratios, Mergers and Acquisitions